A fenomenologia do corpo e subjetividade em Michel Henry - Bonilha, Luiz Edmundo Pinto (2017)
The aim of this work is to present the phisosophy elaborated by Michel Henry, focusing on the theme related to the being of the subjective body that is constituited by „movement‟. Therefore, it belongs to the sphere of absolute immanence which is subjectivity. Under rhe influence of Maine de Biran‟s philosophy, Henry developed a phenomenologic ontology, which had as objective to present not a biologic body or an „adornment‟ of the soul in which knownledge runs out, being relegated to transcendence, but a subjective body that belongs to the sphere of radical absolute imanence. Through the movements of the body, there is an „ontological possibility‟ of knowning the world, the colors, odors, that is, everything around me. Thus, this research focused on the work „Philosophie et phénoménologie du corps: essai sur l'ontologie biranienne‟ as corpus, because from this it is possible to understand how the movement can be considered something that belongs tho the sphere of absolute imanence, and also identifies it with ego.